Green synthesis of ZnO nanoparticles using peels of Citrus limetta and evaluation of their antibacterial activity - Thenmozhi, J R; S, Shahanaz; Manuel, Suba G A (Creative Pharma Assent, 2023)
Background: The fruit peel wastes produced during the processing of different agriculture-related products after production are not utilized to their full potential, and their environmental impact has become a significant global issue. Citrus peel waste is rich in nutrients and has biopotential activity. Objective: The main objective of the current study is to analyze peels of Citrus limetta qualitatively and quantitatively and synthesize Zinc oxide Nanoparticles using the green synthesis method. Methodology: The synthesized ZnO NPs were characterized by UV-visible spectroscopy (UV-Vis), X-ray diffraction (XRD), and Scanning electron microscopy (SEM). The antibacterial activity of C. limetta peels ZnO NPs against Pseudomonas aeruginosa was evaluated by the Agar Disc Diffusion method. Results: The UV-Vis spectrum was measured in the 200 – 400 nm range, and the crystalline structure was analyzed via XRD. SEM/EDS analysis confirmed the nano-spherical structures and the agglomeration of the synthesized ZnO NPs. A minimal inhibitory effect against the Pseudomonas aeruginosa by C. limetta peels ZnO NPs was observed. Conclusion: Hence, the green synthesized ZnO NPs offer an effective and economical way to utilize citrus peel waste in both food and non-food sectors.